Upcoming Special Issue: “Artificial Intelligence, Data Science and E-health in Vision Research and Clinical Activity” - González-Méijome, José Manuel (2022)
[Excerpt] Over the past 13 years Journal of Optometry has published a significant amount of scientific and clinical information covered in over 450 manuscripts published with Original Articles and Review Articles representing over 76% of all the documents making the journal rank high in the international databases.1,2 Considering the emerging technological advances applied to visual sciences the Journal will publish a Special Issue to include novel scientific contributions and novel applications of different branches of artificial intelligence, data science and other approaches to digitalization of vision science research and clinical activity. From basic visual function testing of visual acuity or contrast sensitivity3 to complex screening and diagnostic tools including visual field evaluation technology4 is about to change the paradigm of applying screening testing in flexible, portable and self-used platforms. This has the potential of expanding the capability of the population to self-screen their vision, receive warning messages to visit a clinician and potentially promote early diagnosis. This is also an opportunity to obtain massive amounts of data that might improve our understanding of visual science and vision health provision around the World. [...]